A new species of Omolicna (Hemiptera: Auchenorrhyncha: Fulgoroidea: Derbidae) from coconut palm in Costa Rica and new country records for Omolicna brunnea and Omolicna triata - Bahder, Brian W.; Bartlett, Charles R.; Barrantes, Edwin A. Barrantes; Echavarria, Marco A. Zumbado; Humphries, Alessandra R.; Helmick, Ericka E.; Ascunce, Marina S.; Humphries, Alessandra R.; Helmick, Ericka E.; Ascunce, Marina S.; Goss, Erica M. (Zootaxa, 2019)
An ongoing survey for novel phytoplasmas and viruses that affect palms (Arecaceae) is being conducted in Costa Rica along with potential vectors. During that survey, a new species of derbid planthopper (Hemiptera: Fulgoroidea) in the genus Omolicna Fennah was detected from Heredia and Limón State and is here described as Omolicna xavieri sp. n. This new taxon was first found on declining coconut palms (Cocos nucifera) and subsequently on healthy coconut palms in Tortuguero National Park. Also, two additional species of Omolicna, O. brunnea and O. triata, were collected on coconut in the same habitat and represent new country records. There are no previously published records of Omolicna from Costa Rica. Sequence data for the cytochrome c oxidase subunit I (COI) and the 18S ribosomal RNA gene were obtained. In addition, novel 18S primers specific to auchenorrhynchan insects were developed and presented. The molecular data show high pairwise distances between O. xavieri sp. n. and other Omolicna species (24% to 31% and 10% using COI and 18S, respectively). Based on both morphological and sequence data, we erect and briefly describe the new subgenus Agoo for the new species to reflect the observed differences. A checklist of Omolicna species is presented.